2009
DOI: 10.1007/s00405-009-1072-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in auditory ossicles in rheumatoid arthritis: scanning electron microscopic study

Abstract: The aim of this study was to define the existence of surface changes on auditory ossicles caused by rheumatoid arthritis. The study comprised of nine pairs of auditory ossicles (mallei and incudes) from autopsy of patients with rheumatoid arthritis, and five pairs of ossicles from persons without RA, taken during autopsies. The specimens were studied with JEOL JSM 5300 type scanning electron microscope. Surface changes of auditory ossicles were defined, affected areas were calculated, and expressed in percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Scanning electron microscopic study of auditory ossicles from patients with RA confirmed significantly higher incidence of surface and articular changes. Longer duration of disease caused more intense ossicular alterations [15]. Hearing was worse in older patients, with longer duration of disease, with active disease, and RA nodules.…”
Section: Discussionmentioning
confidence: 97%
“…Scanning electron microscopic study of auditory ossicles from patients with RA confirmed significantly higher incidence of surface and articular changes. Longer duration of disease caused more intense ossicular alterations [15]. Hearing was worse in older patients, with longer duration of disease, with active disease, and RA nodules.…”
Section: Discussionmentioning
confidence: 97%
“…Although hearing impairment occurs frequently in patients with autoimmune disease, the pathogenesis of hearing impairment remains controversial [ 13 , 15 ]. Bone defects in the middle ear were observed in murine models of RA and destruction of the incudostapedial and incudomalleolar joints can result in impaired conduction [ 18 , 34 ]. However, it does not necessarily lead to a hearing impairment [ 6 , 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural hearing loss was the most common hearing impairment, occurring in up to 80% of cases, following by conductive hearing loss [ 13 , 15 ]. While conductive hearing loss can be caused by arthritis of the incudostapedial and incudomalleolar joints, sensorineural hearing loss can be associated with inflammation of the inner ear, as well as vasculitis, neuritis, or deposition of immune complex, which result in cochlear damage [ 15 - 18 ]. The risk factors for hearing impairment in RA include old age, male, long disease duration, and anti-citrullinated peptide antibody (ACPA) positivity [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque algunos autores hacen énfasis en la naturaleza neurosensorial de la hipoacusia, otros consideran el oído medio como el blanco primario de la enfermedad 19,20 .…”
Section: Discussionunclassified